Profile of Students' Mathematical Critical Thinking Ability in Solving Flat Sides Geometry Problems - Zakiyah, Mar’atuz; Maimunah, Maimunah; Suanto, Elfis (FKIP Universitas Lampung, 2022)
Mathematical critical thinking is an important ability in learning mathematics. In fact, students' mathematical critical thinking ability still low. The purpose of this study to analyze students' mathematical critical thinking ability in the flat sided spaces material. This type of research is a descriptive qualitative, with subject students of class IX MTs Miftahuddin. The instruments are tests of mathematical critical thinking ability and interview guidelines. The test to determine students' mathematical critical thinking skills and interview guidelines to deepen the analysis. The result is each student can meet different indicators. Overall, the average mathematical critical thinking ability of MTs Miftahuddin students in solving flat sided space material is high. Because students understand the material well and use to solving questions in the form of word problems. Indirectly, students have carried to indicators of mathematical critical thinking ability.Keywords: profile of critical thinking ability, flat side space. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1527-1538